A Pilot Study for Targeted Surveillance of Bovine Spongiform Encephalopathy in Nigeria. Issue 3 (18th May 2012) - Nwankiti, O. O.; Ikeh, E. I.; Asala, O.; Seuberlich, T.
Summary Bovine spongiform encephalopathy (BSE), popularly known as 'mad cow disease', led to an epidemic in Europe that peaked in the mid‐1990s. Its impact on developing countries, such as Nigeria, has not been fully established as information on livestock and surveillance has eluded those in charge of this task. The BSE risk to Nigeria's cattle population currently remains undetermined, which has resulted in international trade restrictions on commodities from the cattle population. This is mainly because of a lack of updated BSE risk assessments and disease surveillance data. To evaluate the feasibility of BSE surveillance in Nigeria, we carried out a pilot study targeting cattle that were presented for emergency or casualty slaughter. In total, 1551 cattle of local breeds, aged 24 months and above were clinically examined. Ataxia, recumbency and other neurological signs were topmost on our list of criteria. A total of 96 cattle, which correspond to 6.2%, presented clinical signs that supported a suspect of BSE. The caudal brainstem tissues of these animals were collected post‐mortem and analysed for the disease‐specific form of the prion protein using a rapid test approved by the International Animal Health Organization (OIE). None of the samples were positive for BSE. Although our findings do not exclude the presence of BSE in Nigeria, they do demonstrate that targeted sampling of clinically suspected cases of BSE is feasible in developing countries. In addition, these findings point to the possibility of implementing clinical monitoring schemes for BSE and potentially other diseases with grave economic and public health consequences.